Financial stability and secure currency in a modern context - Jan A. Kregel (Levy Economics Institute of Bard College, 2016)
Against the background of modern-day monetary proposals, ranging from a return to the gold standard to the wholesale abolition of currency, this paper seeks to draw implications from David Ricardo's Proposals for an Economical and Secure Currency for plans to reform the operation of central banks and extraordinary monetary policy. Although 200 years old, the 'Ingot plan,' proposed during a period in which gold convertibility was suspended, appears to be applicable to modern monetary conditions and suggests possible avenues of reform.
Keywords: B12; E42; N10; 330; David Ricardo; Monetary Systems; Ingot Plan; Gold Standard